Analysis of dental morbidity of employees of a chemical enterprise - A. M. Fulova; P. A. Ryazantseva; D. A. Ostanina; A. V. Mitronin; A. D. Baitokova (Эндодонтия Today)
INTRODUCTION. In the course of work, a complex of industrial hazards negatively affects the health of employees of chemical enterprises, among which dental morbidity occupies a significant place. To assess the risk of professional dental erosion, it is necessary to obtain more data on the dental status of employees of industrial enterprises.AIM. To study the dental status of employees of chemical and pharmaceutical production, depending on their work experience, in order to increase the effectiveness of early diagnosis, prevention and treatment of patients with systemic lesions of hard dental tissues.MATERIALS AND METHODS. The clinical examination involved 60 patients aged 25 to 60 years, who were divided into two groups according to work experience: Group I – work experience up to 5 years (n = 22); Group II – work experience 5–10 years (n = 38). The patients underwent: determination of the the index of the prevalence and intensity of caries, the Greene-Wermillion index, the basic erosive erasability index (BEWE – basic erosive wear examination) and pH-metry of mixed saliva.RESULTS. In patients of Group I, in comparison with patients of Group II, there is a higher activity of the carious process and poor oral hygiene. With increasing age and length of service, there is a significant increase in the proportion of employees with dental erosion. In Group I patients, the saliva hydrogen index is lower compared to patients in Group II.CONCLUSIONS. Among the workers of chemical enterprises, there is a great need for oral sanitation, since the influence of harmful production factors on the severity of dental pathology has been proven.